A review of the cavernicolous genus Guiaphaenops Deuve, with the description of a new species (Coleoptera, Carabidae, Trechinae) - Feng, Bin (Zookeys, 2017)
Abstract. The subterranean ground beetle genus Guiaphaenops Deuve, 2002 is taxonomically reviewed. This poorly known genus is different from Guizhaphaenops Vigna Taglianti, 1997 in having convex propleura which is visible from above and elytral chaetotaxy especially the humeral group of the marginal umbilicate series, in which the 1(st) pore is transversely and backwardly shifted. The second species, G. deuvei Tian, Feng & Wei, sp. n., is described from a limestone cave at Yangli Cun (Village), Lingyun Xian (County), Baise Shi (Prefecture), northwestern Guangxi Zhuang Autonomous Region, China. A key to the species and a distribution map of Guiaphaenops are also provided.